Longitudinal Study of Viral and Bacterial Contamination of Hospital Pediatricians’ Mobile Phones - Cantais, Aymeric (Microorganisms, 2020)
Mobile phones (MPs) of healthcare workers (HCWs) may represent an important source of transmission of infectious agents. This longitudinal study documents the contamination of these tools. Ten MPs handled by senior pediatricians were sampled once a week during 23 weeks in three pediatric wards of the University Hospital of Saint-Etienne, France. Cultures were performed for bacteria and multiplex PCR assays for a panel of respiratory and enteric viruses. A questionnaire on hygiene habits regarding phoning and care was filled-in by pediatricians before and after the study. From a total of 230 samples, 145 (63%) were contaminated by at least one pathogen. The MPs from emergency departments were the most impacted. Viruses were detected in 179 samples; bacteria were isolated in 59 samples. Contamination increased during the winter epidemic peak. A cross-contamination by Paracoccus yeei between hands and MPs of different HCWs was demonstrated. The communication of the study results influenced the hygiene behaviors. This study highlights the contamination of MPs by pathogens that are resistant in the environment, and its sustainability along the winter season. The role of MPs as vectors of nosocomial infection needs to be better investigated.